2013
DOI: 10.1016/j.juro.2013.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve of Robotic Assisted Pyeloplasty for Pediatric Urology Fellows

Abstract: DISCLAIMER Purpose Little is known about the learning curve of robotic surgery for surgeons-in-training. We hypothesized that pediatric urology fellows could attain proficiency in robotic pyeloplasty, defined as an operative time equivalent to that of an experienced robotic surgeon, within the two-year time frame of fellowship. Material and Methods From 2006 – 2010, we performed a prospective cohort study of four pediatric urology fellows and one pediatric urology attending performing pediatric robotic pye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 11 publications
1
47
0
3
Order By: Relevance
“…These terms, however, were used inconsistently or interchangeably 36,50 , or used with distinct definitions 33,49 . These terms, however, were used inconsistently or interchangeably 36,50 , or used with distinct definitions 33,49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These terms, however, were used inconsistently or interchangeably 36,50 , or used with distinct definitions 33,49 . These terms, however, were used inconsistently or interchangeably 36,50 , or used with distinct definitions 33,49 .…”
Section: Discussionmentioning
confidence: 99%
“…In 13 of 14 studies (93 per cent) that employed performance terms, at least one term was used to describe the point where the learning curve had been overcome; 'proficiency' was used for this purpose in ten studies 22,27,28,31,36,38,39,42,50,55 , 'competency' in five studies 10,27,33,36,49 and 'expertise' in one study 50 . However, these terms were used inconsistently.…”
Section: Standards Of Reportingmentioning
confidence: 99%
“…Since volume-outcome relationships are a well-described phenomenon across multiple surgical specialties, a drop in cases gives pause for concern. Indeed superior outcomes have been demonstrated in association with volume or specialty training for pediatric extracorporeal membrane oxygenation (ECMO) [10,11], pyloromyotomy [12,13], appendectomy [14], urology [15,16], and cardiac surgery [17].…”
Section: Deliberate Practice In Surgical Educationmentioning
confidence: 99%
“…The learning curve has been shown to be shorter, with outcomes comparable to those of open procedures [35,51,52]. Many publications have reported that the introduction of robotics after a well-conducted training program is safe and effective [53,54]. In a recent prospective cohort study to determine the learning curve for paediatric urology fellows in paediatric robotic pyeloplasty, the authors concluded that the operative time for robotic pyeloplasty performed by fellows consistently decreased with cumulative surgical experience [54].…”
Section: Robotic Assisted Surgerymentioning
confidence: 99%
“…Many publications have reported that the introduction of robotics after a well-conducted training program is safe and effective [53,54]. In a recent prospective cohort study to determine the learning curve for paediatric urology fellows in paediatric robotic pyeloplasty, the authors concluded that the operative time for robotic pyeloplasty performed by fellows consistently decreased with cumulative surgical experience [54]. Another recent publication highlighted the value of a multitechnique robotic training curriculum including dry-lab in addition to virtual and clinical training in the use of the robotic platform [55].…”
Section: Robotic Assisted Surgerymentioning
confidence: 99%